1970
DOI: 10.1210/endo-87-5-850
|View full text |Cite
|
Sign up to set email alerts
|

Circhoral Oscillations of Plasma LH Levels in the Ovariectomized Rhesus Monkey1,2

Abstract: Blood samples were withdrawn at 10-, 20-or 30-min intervals for 6-12 hr from 13 ovariectomized and 7 intact female rhesus monkeys bearing indwelling cardiac catheters and restrained in primate chairs. Plasma LH and GH concentrations were determined by radioimmunoassay. Twenty-four experiments in ovariectomized animals revealed a striking rhythmic pattern in plasma LH levels having a period of approximately 1 hr, which was asynchronous with variations in plasma GH concentrations when these occurred. The LH osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
120
1
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(133 citation statements)
references
References 5 publications
8
120
1
3
Order By: Relevance
“…In the adult ovariectomized monkey, the circhoral release of GnRH results in mean levels of circulating LH ranging in general from 100 to 200 ng/ml (Dierschke et al 1970), concentrations which were frequently observed in the present study in response to the nocturnal release of pulsatile GnRH from the hypothalamus of the 15-to 20-month-old female. While the relationship between frequency and amplitude modulation of a pulsatile pattern of GnRH stimulation, on the one hand, and its strength as a drive to the gonadotroph, on the other, is complex, similar levels of mean LH are intuitively equated to comparable GnRH drives.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the adult ovariectomized monkey, the circhoral release of GnRH results in mean levels of circulating LH ranging in general from 100 to 200 ng/ml (Dierschke et al 1970), concentrations which were frequently observed in the present study in response to the nocturnal release of pulsatile GnRH from the hypothalamus of the 15-to 20-month-old female. While the relationship between frequency and amplitude modulation of a pulsatile pattern of GnRH stimulation, on the one hand, and its strength as a drive to the gonadotroph, on the other, is complex, similar levels of mean LH are intuitively equated to comparable GnRH drives.…”
Section: Discussionsupporting
confidence: 69%
“…In such studies, inter-GnRH-pulse intervals of approximately 1 h have been described for juvenile ovariectomized monkeys . In adult ovariectomized monkeys, direct and indirect assessment of GnRH pulse frequency has yielded comparable estimates of this parameter, namely approximately 1 pulse/h (Dierschke et al 1970, Wilson et al 1984, Gearing & Terasawa 1991. Since the present indirect analysis of GnRH pulse frequency in the prepubertal animal employed a pituitary with a responsiveness similar to that in the adult, the lack of congruency between the results obtained by the two methods in the prepubertal state must therefore be related to the smaller GnRH signal at this stage of development.…”
Section: Discussionmentioning
confidence: 71%
“…First, surgery can affect pain thresholds [93,173] and sensitivity to analgesics. Second, gonadectomy disrupts the normal feedback loop that sex steroids exert on the anterior pituitary and hypothalamus, leaving both males and females in a prolonged state of elevated (e.g., gonadotropin-releasing hormone (GnRH), leuteinizing hormone) or depressed (e.g., prolactin) circulating hormones [1,53,95,220]. The likelihood of unintended consequences due to altered hypothalamic/pituitary hormone secretion can be addressed by administering low (maintenance) doses of estradiol or testosterone rather than using gonadectomized animals with no hormone replacement.…”
Section: Hormone Manipulations: Animal Studiesmentioning
confidence: 99%
“…Had it not been for Harris' untimely death at an age of 58 he surely would have shared this most prestigious of awards for laying the conceptual underpinnings for the work of Schally and Guilleman! In 1969, two years before Schally and Guilleman reported the isolation of GnRH, Knobil's laboratory studying the ovariectomized rhesus monkey had found that LH was secreted in a pulsatile or episodic manner with a frequency in the agonadal condition of approximately 1 pulse per hour: they proposed that this pulsatile mode of LH secretion may be due to intermittent signals from the central nervous system that are relayed to the pituitary by an LH releasing factor (Dierschke, et al 1970;Knobil 1992). Knobil's laboratory went on to demonstrate in 1978 that intermittent GnRH stimulation of the pituitary was essential for sustained secretion of both LH and FSH (Belchetz, et al 1978) (Figure 2).…”
Section: Introductionmentioning
confidence: 99%